2012
DOI: 10.1111/ene.12017
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of newly diagnosed atrial fibrillation in cryptogenic stroke: a cohort study

Abstract: In cryptogenic ischaemic stroke, the NDAF score can be used to target patients at high risk of developing AF after hospital discharge, as a score of 0-1 was highly predictive of the absence of NDAF during follow-up. These results need to be confirmed in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 45 publications
5
58
1
Order By: Relevance
“…One limitation is that we did not have data regarding left atrial size or left ventricular ejection fraction, which are independent risk factors for AF development. 22 Another limitation is that we did not have information about treatment before admission that could affect pro-BNP levels. In addition, we did not investigate the temporal profile of pro-BNP, and some studies found that pro-BNP levels decrease in the days following a stroke.…”
Section: Resultsmentioning
confidence: 99%
“…One limitation is that we did not have data regarding left atrial size or left ventricular ejection fraction, which are independent risk factors for AF development. 22 Another limitation is that we did not have information about treatment before admission that could affect pro-BNP levels. In addition, we did not investigate the temporal profile of pro-BNP, and some studies found that pro-BNP levels decrease in the days following a stroke.…”
Section: Resultsmentioning
confidence: 99%
“…However, cost-effective analysis is currently lacking to support the wide-spread use of these expensive devices, particularly implanted cardiac monitors, in the post stroke population. Scoring systems have been developed to predict post-stroke atrial fibrillation [15,2327]; yet these studies are inconclusive due to small sample size, short monitoring period, difficulty in data acquisition, or poor applicability to the CS/TIA population. Our study was conducted to address this pressing need to properly triage resources in stroke patients without manifest AF beyond the initial 30-day window.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors assessed were hypertension (HTN), diabetes (DM), obesity defined by BMI>30, systolic and/or diastolic heart failure (CHF), coronary artery disease (CAD), peripheral vascular disease (PVD), chronic kidney disease (CKD) stage III, IV, V, aortic valve disease, mitral valve disease, tricuspid valve disease, and pulmonary valve disease. Such clinical factors are well known to be risk factors for AF [15,16]. A comprehensive list of conditions covered by each respective ICD-9 used is detailed in the supplemental table.…”
Section: Methodsmentioning
confidence: 99%
“…Several risk factors have been reported (Table 3), and some risk-stratification scores have been proposed. 22,[41][42][43][44][45][46][47] Older age is the factor most consistently associated with higher risk of AF, and this risk increases with the accumulation of vascular risk factors and in patients with documented vascular disease. Thus, most patients with stroke already have some of the main risk factors for AF.…”
Section: Best Candidates For Prolonged Monitoringmentioning
confidence: 99%
“…Yet, findings on brain imaging (embolic pattern), 41,42 ECG/Holter (frequent premature atrial complexes), 22,29,43 and echocardiography (left atrial dilatation on transthoracic and perhaps reduced left atrial appendage ejection fraction on transesophageal echocardiogram) can help stratify the risk further. 22,[45][46][47] It is reasonable to restrict prolonged ambulatory cardiac rhythm monitoring to patients with stroke deemed cyptogenic after a comprehensive evaluation and an embolic pattern on brain imaging (multiterritorial or single cortical-subcortical infarctions). Monitoring should be initiated early after the cerebrovascular event to maximize the detection yield.…”
Section: Best Candidates For Prolonged Monitoringmentioning
confidence: 99%